2012
DOI: 10.1098/rstb.2011.0296
|View full text |Cite
|
Sign up to set email alerts
|

Host genetics and population structure effects on parasitic disease

Abstract: Host genetic factors exert significant influences on differential susceptibility to many infectious diseases. In addition, population structure of both host and parasite may influence disease distribution patterns. In this study, we assess the effects of population structure on infectious disease in two populations in which host genetic factors influencing susceptibility to parasitic disease have been extensively studied. The first population is the Jirel population of eastern Nepal that has been the subject o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Other studies that highlight the role that protozoan parasites had in shaping the genetics of human populations were recently reviewed [129]. These studies suggest that quantitative trait loci and/or human polymorphisms play a role in genetic susceptibility to parasite burden and/or associated pathology for different pathogens of human [130][131][132][133] and livestock [134,135]. These types of investigations, however, require large cohorts of individuals (patients or animals), generate large sequence data sets, and usually lack causal conclusions.…”
Section: Host Genetics: the Neglected Side Of The Host-pathogen Intermentioning
confidence: 99%
“…Other studies that highlight the role that protozoan parasites had in shaping the genetics of human populations were recently reviewed [129]. These studies suggest that quantitative trait loci and/or human polymorphisms play a role in genetic susceptibility to parasite burden and/or associated pathology for different pathogens of human [130][131][132][133] and livestock [134,135]. These types of investigations, however, require large cohorts of individuals (patients or animals), generate large sequence data sets, and usually lack causal conclusions.…”
Section: Host Genetics: the Neglected Side Of The Host-pathogen Intermentioning
confidence: 99%
“…Individual predisposition to get infected by heavy or light worm loads is maintained in treatmentreinfection studies [32], and aggregates in families [33,34]. Epidemiological studies revealed than in addition to exposure and household determinants, genetic factors account for an important proportion of the variation in worm loads [35][36][37][38].…”
Section: Immunogenetics Of the Ige Responses To Ascaris And Allergensmentioning
confidence: 99%
“…Williams-Blangero et al [50] was the first to use single nucleotide polymorphism typing in Chagas disease to explore genetic determinants of susceptibility and cardiovascular progression of disease in humans. Research by Wen et al [51] focused on improving the ability to diagnose Chagas disease identified a proteomic signature for patients with CCC to allow for earlier detection of disease.…”
Section: Nhlbi–funded Research On Chagas Diseasementioning
confidence: 99%